Problems encounted by English Department Students in Composing a coherent paragraph - Noor, Infan user (Muadalah, 2013)
ncdddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddew